(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hypertension (HTN) is a significant global health concern, affecting millions of individuals and contributing to cardiovascular diseases such as heart attacks and strokes. One of the primary mechanisms underlying hypertension is oxidative stress, which results from an imbalance between reactive oxygen species (ROS) and the body’s antioxidant defenses. Excessive ROS levels lead to endothelial dysfunction, vasoconstriction, inflammation, and increased arterial stiffness, all of which contribute to elevated blood pressure. This paper explores the complex mechanisms through which oxidative stress contributes to hypertension, including the role of nitric oxide synthase dysregulation, mitochondrial dysfunction, and inflammatory pathways. The interaction between oxidative stress and the renin- angiotensin-aldosterone system (RAAS) is also discussed, highlighting how oxidative damage exacerbates hypertensive conditions.